2003
DOI: 10.1074/jbc.m304843200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Cone Snail Protease with Homology to CRISP Proteins of the Pathogenesis-related Protein Superfamily

Abstract: The pathogenesis-related (PR) protein superfamily is widely distributed in the animal, plant, and fungal kingdoms and is implicated in human brain tumor growth and plant pathogenesis. The precise biological activity of PR proteins, however, has remained elusive. Here we report the characterization, cloning and structural homology modeling of Tex31 from the venom duct of Conus textile. Tex31 was isolated to >95% purity by activityguided fractionation using a para-nitroanilide substrate based on the putative cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
206
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(211 citation statements)
references
References 33 publications
(27 reference statements)
2
206
1
2
Order By: Relevance
“…suggest that CAP domains may have enzymatic (Milne et al, 2003), immunological (Moyle et al, 1994), or cellular adhesion functions (Maeda et al, 1999). A more detailed understanding of the expression profile of CRISPs provides insights into their potential biological functions.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…suggest that CAP domains may have enzymatic (Milne et al, 2003), immunological (Moyle et al, 1994), or cellular adhesion functions (Maeda et al, 1999). A more detailed understanding of the expression profile of CRISPs provides insights into their potential biological functions.…”
Section: Figmentioning
confidence: 99%
“…All members of this family share a common CAP domain (also known as a sperm-coating protein, SCP, domain or a PR-1 domain), which is characterized by the presence of two signature motifs that are involved in the formation of a cleft-like structure forming a putative active site containing (in the CRISPs) three intra-molecular disulphide bonds (Henriksen et al, 2001;Shikamoto et al, 2005). CAPs are typically secreted and found in an extraordinary range of species in both bacteria and eukaryotes including, for example, yeast, fungi, plants, cone snails, drosophila, lampreys, snakes, mice, and humans (Pfitzner and Goodman, 1987;Schuren et al, 1993;Miosga et al, 1995;Murphy et al, 1995;Schreiber et al, 1997;Yamazaki et al, 2002b;Milne et al, 2003;Ito et al, 2007)). The presence of such an evolutionarily diverse, yet conserved, structure is suggestive of a common function, although the identification of this function remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, protease activity has been suggested as a shared feature of PR-1 proteins based on structure-function inference from the cone snail protease Tex31 (Milne et al, 2003), but could not be demonstrated to date. We were intrigued by the structural similarity of the tandem histidine motif of Group 1 ASPs with enzymatic sites found in phosphodiesterases such as the Arabidopsis CPDase (Hofmann et al, 2000b), and thus investigated the possibility that Na-ASP-2 might possess phosphohydrolase activity.…”
Section: Enzymatic Activitymentioning
confidence: 99%
“…Proteolytic activity has been speculated for this protein based on enzymatic activity observed for cone snail protease Tex31, a member of the CRISP family of pathogenesis-related proteins (Milne et al, 2003). Proteolytic activity was not detected for Na-ASP-1 or ASP-2, and from the crystal structure of the protein it is obvious that the proposed residues for this activity are not in spatial vicinity.…”
Section: Introductionmentioning
confidence: 99%